THE INFLUENCES OF NATURAL GAS IMPURITIES TO THE SURFACE TENSION OF BLENDED PIPERAZINE-N-METHYLDIETHANOLAMINE (MDEA) SOLUTION - Iwan Ratman; Ahmad Fauzi Ismail (Dept. of Chemical Engineering, Diponegoro University, 2008)
This study focuses on the effect of impurities in the natural gas stream on the characteristic of surface tension in the blended piperazine and MDEA solution. Hydrocarbon liquids, Iron Sulphide, Sodium Chloride, Acetic Acid, Methanol and Polyethylene Glycol were used as the impurities. The results indicated that the type of impurities determined the surface tension changes of the amine solution. The concentration of piperazine-MDEA blends also enhanced to the increasing of surface tension. Iron sulphide, hydrocarbons and sodium chloride as the impurities in the amine solution were the most influential factors to the surface tension. Statistical experimental method was employed to determine the main effect in the increasing of surface tension. Full factorial design and response surface methodology (RSM) coupled with central composite design (CCD) were used to determine the increasing of surface tension in the amine solution. A central composite design was used to determine the main variables such as iron sulphide, hydrocarbon and sodium chloride. The maximum surface tension of 74.33 mNm-1 was determined at the combined impurities concentrations of Iron Sulphide at 6.346 ppm, Hydrocarbon liquids at 11.827 ppm and Sodium Chloride at 8.261 ppm.Pada penelitian ini difokuskan untuk mengetahui pengaruh impuritas didalam aliran gas alam terhadap karakteristik tegangan permukaannya pada campuran larutan MDEA-piperazin. Hidrokarbon, besi sulfida, NaCl, asam asetat, methanol dan PEG digunakan sebagai larutan impuritas pada gas alam. Pada penelitian ini menunjukan bahwa jenis dari impuritas akan mempengaruhi besarnya tegangan permukaan yang dihasilkan pada larutan amin. Konsentrasi larutan amin juga mempengaruhi tegangan permukaan yang dihasilkan. Besi sulfida, hidrokarbon dan NaCl adalah faktor penting yang menentukan besanya tegangan permukaan yang dihasilkan. Metode statistik yang menggunakan response surface methodology (RSM) yang digabungkan dengan central composite design (CCD) telah digunakan untuk mengetahui faktor utama yang menentukan tegangan permukaan. Tegangan permukaan yang paling tinggi dihasilkan pada konsentrasi besi sulfida 6,346 ppm, hidrokarbon 11,827 ppm dan NaCl 8,261 ppm adalah sebesar 74,33 mNm-1.